Form of Spatial Flexibility in Lanting House Dwellings in Palangka Raya City - Febrian Rizqi Antony; Dewi Septanti; Didit Novianto (Green Publisher Indonesia, 2025)
The geographical condition of Kalimantan Island, which has many rivers, indirectly influences the formation of the city’s character. This condition led to the formation of river culture or defined as a civilization based around rivers. This led to the presence of lanting houses as an architectural product resulting from river culture. The issue that is currently developing is maintaining the architectural products of lanting houses, which are the identity of the City of Palangka Raya and must be preserved. The problem that occurs is that residents of lanting houses have challenges, namely limited space. Limited space makes residents of lanting houses use the space in lanting houses as efficiently as possible. Lanting house residents adapt to complex and varied activities by adjusting the space in the lanting house. This research examines the form of an individual’s ability to adapt to limited space through spatial flexibility in a lanting house. This research uses a mixed method to review phenomena based on experiences with architecture. The phenomenon referred to in this research is the experience of the residents of the lanting house regarding limited space. It is hoped that this research can provide an overview of the forms of spatial flexibility that occur in limited spaces in buildings on water or lanting houses in Palangka Raya City. The research implications contribute to sustainable housing development strategies for riverine communities, inform cultural preservation policies for traditional architecture, and provide design guidelines for space-efficient dwelling solutions in water-based settlements.